Perbedaan Kepuasan Pasien Yang Menggunakan Jaminan Kesehatan Dirawat Inap Di Ruang Kebidanan Rumah Sakit Pemerintah Dengan Swasta Tahun 2017 - I Gusti Ayu Surati; Gusti Ayu Marhaeni; Ni Wayan Armini (Poltekkes Kemenkes Denpasar, 2018)
Health coverage in the form of health protection in order that participants benefit health maintenance and protection of funds provided to any person who has paid dues. The purpose of the study to analyze the difference in Satisfaction patients using health coverage that is admitted in the Obstetrics Hospital Government with private sector based on dimensions: Tangibles, Reliability, Responsiveness, Assurance, Emphaty. The hypothesis of this research there is a difference of satisfaction patients using health coverage are admitted in government hospitals with Obstetrics. This research was carried out at Government and private Hospitals in the city of Denpasar years 2017, with no significant difference between a government hospital with private hospitals of patient satisfaction dimension includes tangibility (P value 0.425), reliability (P value 0.802), Responsiveness (P value 0.337), assurance (P value 0.808, and empathy (P value 0.960) in patients using health coverage in the inpatient obstetrics government hospitals with private hospitals the year 2017